Changes in and Modelling of Hydrological Process for a Semi-Arid Catchment in the Context of Human Disturbance - Liu, Yue; Zhang, Jianyun; Yang, Qinli; Zhou, Xiong; Wang, Guoqing (Frontiers in Earth Science, 2021)
Hydrological modelling is of critical importance to flood control. However, flood forecasting in semi-arid region is a great challenge to hydrologists, particularly in a changing environment. Taking the Zhulong River catchment located in north China as a case, the performance of GR4J model for hydrological modelling was investigated based on the analysis for changes in hydrological process of three periods defined as natural period (1967–1979), moderate human impact period (1980–1996) and intensive human impact period (1997–2015). Results show that 1) the annual precipitation and temperature of the catchment both presented upward trends, while the annual observed runoff exhibited a significant downward trend in the time span from 1967 to 2015; 2) the correlations between runoff and precipitation were comparatively higher on both monthly and annual scales in natural period than those in human disturbed periods; 3) both annual runoff and daily peak discharge in human disturbed periods decreased relative to those in natural period due to the environmental changes; 4) the GR4J model performed well for runoff simulations in natural period but gradually lost its applicability with the intensification of human activities. It is essential to improve the accuracy of hydrological modelling under a changing environment in further studies.